Spectrum of imaging findings of papillary breast disease: A radiopathological review in a tertiary center. Issue 16 (23rd April 2021) - Fadzli, Farhana; Rahmat, Kartini; Ramli, Marlina Tanty; Rozalli, Faizatul Izza; Hooi, Teoh Kean; Fadzli, Ahmad Nazran; Hoong, See Mee; Ramli, Norlisah Mohd; Taib, Nur Aishah Mohd
Abstract : Abstract: To evaluate the clinical and imaging findings of papillary breast neoplasm and review the pathologic correlation at a tertiary center. Retrospective study of patients diagnosed with benign and malignant papillary lesions between 2008 to 2018. 147 patients were identified with histology diagnosis of papillary lesions. The clinical, imaging, and pathological characteristics were reviewed. Patient cohort included 147 women diagnosed with papillary lesions (mean age at diagnosis 53.8 years) and were divided into 3 histology groups (benign, atypical, and malignant). Common clinical presentations were breast lump (n = 60) and nipple discharge (n = 29), 48 patients were asymptomatic. Only 37 were detected as a mass lesion on mammogram. The presence of mass lesion on mammogram was the most common feature in all 3 papillary lesion groups, and with the presence of asymmetric density, were the 2 mammographic features significantly associated ( P < .05) with malignancy. All lesions were detected on ultrasound. The most common sonographic features for all 3 groups were the presence of a mass and irregular shape. Among all the sonographic features assessed, larger size, presence of vascularity and absence of dilated ducts were significantly associated ( P < .05) with malignancy. Feature pattern recognition of the variety of benign, atypical and malignant papillary neoplasm on ultrasound and mammogram, with emphasis on size, presence of vascularity and dilated ducts on ultrasound and presence of mass, and architectural distortion on mammogram, is important in the assessment of patients with suspected ductal lesions to facilitate optimal treatment and surgical care.